Amulet & Health - Khan, M Karim; Busreea, Reeva Aireen; Noor, Masumatun (Community Based Medical Journal, 2017)
Amulet use is global but it is more prevalent in SEA. Use of amulet in Bangladesh is quite common as well. In case of children it is being used for protecting children from all types of diseases & from all danger. The study was done in Community Based Medical College Hospital Bangladesh Pediatric ward in the month of 5th January, 15 to 8th January 15. It was a cross sectional descriptive type of study. Study population 82 admitted children age between six months to sixty months, average ±18.37 months. Amulets were found in 29.26%, Male 62.50%, female 37.50%. Average cost involvement $1.5 for each amulet. Most of the respondent mother were literate but from low socioeconomic condition. Cause of using amulet mostly, to protect child from diseases & from all dangers according to respondent mother. Amulets were given by grand father or mother, Imam of mosque or by Kabiraj. In response to a question whether it is really protective to child or not, about 40% told that it is effective & the others were not sure or reluctant to pass any comment. CBMJ 2017 July: Vol. 06 No. 02 P: 03-05